The effects of psychotherapy for adult depression on suicidality and hopelessness: A systematic review and meta-analysis - Cuijpers, Pim; De Beurs, Derek P.; Van Spijker, Bregje A.J.; Berking, Matthias; Andersson, Gerhard; Kerkhof, Ad J.F.M. (Journal of Affective Disorders, 2013)
Background: Although treatment guidelines suggest that suicidal patients with depression should be treated for depression with psychotherapy, it is not clear whether these psychological treatments actually reduce suicidal ideation or suicide risk. Methods: We conducted a systematic review and meta-analysis of studies on psychotherapy for depression in which outcomes on suicidality were reported. We also focused on outcomes on hopelessness because this is strongly associated with suicidal behavior in depression. Results: Thirteen studies (with 616 patients) were included, three of which examined the effects of psychotherapy for depression on suicidal ideation and suicide risk, and eleven on hopelessness. No studies were found with suicide attempts or completed suicides as the outcome variables. The effects on suicidal ideation and suicide risk were small (g=0.12; 95% CI: -0.20-0.44) and not statistically significant. A power calculation showed that these studies only had sufficient power to find an effect size of g=0.47. The effects on hopelessness were large (g=1.10; 95% CI: 0.72-1.48) and significant, although heterogeneity was very high. Furthermore, significant publication bias was found. After adjustment of publication bias the effect size was reduced to g=0.60. Discussion: At this point, there is insufficient evidence for the assumption that suicidality in depressed patients can be reduced with psychotherapy for depression. Although psychotherapy of depression may have small positive effects on suicidality, available data suggest that psychotherapy for depression cannot be considered to be a sufficient treatment. The effects on hopelessness are probably higher. © 2012 Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Depression; Meta-analysis; Psychological treatment; Psychotherapy; Suicide